Large-volume paracentesis, up to 27 L, with adjuvant vaginal cabergoline in the case of severe ovarian hyperstimulation syndrome with successful pregnancy outcome: A case report - Nupur Agarwal; Sanghamitra Ghosh; Shikha Bathwal; Baidyanath Chakravarty (Wolters Kluwer Medknow Publications, 2017)
Severe ovarian hyperstimulation syndrome (OHSS) is a potentially life-threatening complication of assisted reproductive technology. Herein, we report the case of an infertile couple, with the husband being azoospermic, who underwent in-vitro fertilisation and intracytoplasmic sperm injection at our institute. The woman presented with late OHSS 7 days after embryo transfer. Inpatient management was performed with intensive surveillance. Oral cabergoline was started prophylactically but was replaced by the vaginal route due to intolerance. Transvaginal paracentesis was performed five times over 20 days, and a total of 27 L of ascitic fluid was drained. The patient improved substantially and had a further uneventful pregnancy course. This case report helped us theorise that large-volume paracentesis is safe and efficacious in the management of severe OHSS. In addition, the vaginal route of cabergoline administration is more favourable than the oral route in view of lesser side effects and better patient compliance.